Lattice character of the refinement structure of Hedge Algebras - Hồ, Nguyễn Cát; Nam, Huỳnh Văn (Journal of Computer Science and Cybernetics, 2016)
Hedge Algebras were  introduced in order to model the natural structure of domains of linguistic variables. In [7], we introduced a refinement structure of Hedge Algebras (RSHA, for short), and some fundamental properties of this structure were examined. In this paper, the main property of the RSHA is given, and it is also shown that many linguistic values, which contain the disjunction and conjunction, can be  expressed in the RSHA. Keywords: PN-consistent hedge algebras, refinement structure of hedge algebras, linguistic valued logic,  linguistic reasoning.